Derivation and characteristics of induced pluripotent stem cells from a patient with acute myelitis - Cao, Shuo; Gao, Xinyue; Liu, Fangyuan; Chen, Yanglin; Na, Qin; Meng, Qiaoqiao; Shao, Peng; Chen, Chen; Song, Yongli; Wu, Baojiang; Li, Xihe; Bao, Siqin (Frontiers in Cell and Developmental Biology, 2023)
The emergence and development of induced pluripotent stem cells (iPSCs) provides an approach to understand the regulatory mechanisms of cell pluripotency and demonstrates the great potential of iPSCs in disease modeling. Acute myelitis defines a group of inflammatory diseases that cause acute nerve damage in spinal cord, however its pathophysiology remains to be elusive. In this study, we derived skin fibroblasts from a patient with acute myelitis (P-HAF) and then reprogrammed P-HAF cells to iPSC using eight exogenous factors (i.e., OCT4, SOX2, c-MYC, KLF4, NANOG, LIN28, RARG, and LRH1). We performed transcriptomic analysis of the P-HAF and compared the biological characteristics of the iPSCs derived from the patient (P-iPSCs) with those derived from normal individuals in terms of pluripotency, transcriptomic characteristics, and differentiation ability toward the ectoderm. Compared to the control iPSCs, the P-iPSCs displayed similar features of pluripotency and comparable capability of ectoderm differentiation in the specified culture. However, when tested in the common medium, the P-iPSCs showed attenuated potential for ectoderm differentiation. The transcriptomic analysis revealed that pathways enriched in P-iPSCs included those involved in WNT signaling. To this end, we treated iPSCs and P-iPSCs with the WNT signaling pathway inhibitor IWR1 during the differentiation process and found that the expression of the ectoderm marker Sox1 was increased significantly in P-iPSCs. This study provides a novel approach to investigate the pathogenesis of acute myelitis.